Novel variants of seryl-tRNA synthetase resulting in HUPRA syndrome featured in pulmonary hypertension - Yang, Fan; Wang, Dan; Zhang, Xuehua; Fan, Haoqin; Zheng, Yu; Xiao, Zhenghui; Chen, Zhi; Xiao, Yunbin; Liu, Qiming (Frontiers in Cardiovascular Medicine, 2023)
Hyperuricemia, pulmonary hypertension, and renal failure in infancy and alkalosis syndrome (HUPRA syndrome) is an ultrarare mitochondrial disease that is characterized by hyperuricemia, pulmonary hypertension, renal failure and alkalosis. seryl-tRNA synthetase 2 (SARS2) gene variants are believed to cause HUPRA syndrome, and these variants result in the loss of function of seryl-tRNA synthetase. Eventually, mutated seryl-tRNA synthetase is unable to catalyze tRNA synthesis and leads to the inhibition of the biosynthesis of mitochondrial proteins. This causes oxidative phosphorylation (OXPHOS) system impairments. To date, 5 mutation sites in the SARS2 gene have been identified. In this study, we discover a novel SARS2 variant that is related to HUPRA syndrome. Whole-exome sequencing revealed novel compound heterozygous variants of SARS2 (c.1205G>A (p.Arg402His) and c.680G>A (p.Arg227Gln)). Computational prediction confirmed that c.680G>A was a novel variant and graded as variants of uncertain significance (VUS). Moreover, this patient had significant pulmonary hypertension and minor renal dysfunction compared with other reported cases.